TERJEMAH DAN TAFSIR DI JAWA AWAL ABAD KE-18: Studi Filologis Bundel Naskah Kajen - Nailis Sa'adah; Muhammad Asif (AL ITQAN: Jurnal Studi Al-Qur'an, 2020)
This study examines the text Terjemah dan Tafsir Surat al-Fatihah (TTSF) contained in the Bundel Naskah Kajen (Bundle of Kajen Manuscripts, BNK) which is attributed to Ahmad Mutamakkin's work. This study aims to describe the manuscript, present the edited text and analyze the translation methods and interpretation of the al-Fatihah verse contained in the BNK. This study uses a philological approach, translation theory and interpretation of al-DhahabÄ«'s perspective. This research found: first, BNK's pension as the work of Ahmad Mutamakkin is very likely to be correct, because referring to Bizawie, the manuscript were written in 1705 AD, during Ahmad Mutamakkin life (1645-1740). Second, the interpretation of the al-Fatihah in the BNK is not like the interpretation of the al-Fatihah verse in general which tends to interpret the al-Fatihah in the context of reverting position (pelungguhan) each word of the al-Fatihah into the anatomy of the human body such as the crown, eye, breath, chest, heart, tongue, skin and other body parts to show the oneness (unity) of being between the servant and his god, which is classified as a á¹£Å«fÄ« naáº“arÄ« interpretation and appropriates the doctrine of waá¸¥dah al-wujÅ«d which was widely developed in the archipelago at that time. Furthermore, the implication of this study is that if this manuscript can be accepted as the work of Ahmad Mutamakkin, it means that the tafsÄ«r writing traditions in Java had started earlier than the previous findings. Keywords: Terjemah dan Tafsir Surah al-Fatihah, Bundel Naskah Kajen, the doctrine of waá¸¥dah al-wujÅ«d.